EU gas infrastructure resilience: Competition, internal changes, and renewable energy pressure. (December 2020) - Sutrisno, Aziiz; Alkemade, Floor
Abstract: Natural gas security has been at the center of European energy policy in the past decade. The perception of future scarcity drives the intention to expand the gas network. However, many of the gas infrastructure expansion plans went in contrast to the spirit of energy security. Such policies lead to a decreasing diversity and expose the system vulnerability for future disruptions. Given recent developments, another gas supply crisis like 2009 might have a different impact. In this study, we investigate the robustness of the current EU gas infrastructure to withstand potential disruptions. We used a network simulation model to simulate the demand and supply balance of the European gas market. The study includes a climatic feature of the gas hubs, potential consumption profile changes, and supply competition with the East Asian market. Our result suggests that the European gas market is not as sensitive as it has in the 2009 crisis despite these challenges. Increasing pipeline connections and new LNG terminals built after 2009 provide spare capacity as the demand growth is slower than expected due to mild winters in recent years. Furthermore, abundant LNG suppliers offer more options to mitigate the price effect and to avoid demand curtailment.